1956
DOI: 10.1161/01.res.4.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulmonary Arterial and Left Atrial Pressures on Pulmonary Vascular Resistance

Abstract: A method has been developed by which flow to each lung, as well as pulmonary artery and left atrial pressures can be measured and varied at will. Vascular resistances were determined over a wide range of these variables. Both pressures have a marked effect on vascular resistances; the higher either pressure, the lower the resistances. This effect is most marked at low levels of pressure and flow. The absolute levels of the pressures, by affecting vascular distension, are major determinants of pulmonary vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 6 publications
(2 reference statements)
10
58
0
1
Order By: Relevance
“…This conclusion is consistent with previous measurements in dogs by Gilbert et al (1958) and West and Dollery (1965). Borst et al (1956) reported a critical closing pressure of 7 mmHg in dog lungs but this was probably an artifact caused by the positive alveolar pressure that was being used to ventilate the lung (West and Dollery 1965). Fig.…”
Section: Zone 3-supporting
confidence: 92%
See 3 more Smart Citations
“…This conclusion is consistent with previous measurements in dogs by Gilbert et al (1958) and West and Dollery (1965). Borst et al (1956) reported a critical closing pressure of 7 mmHg in dog lungs but this was probably an artifact caused by the positive alveolar pressure that was being used to ventilate the lung (West and Dollery 1965). Fig.…”
Section: Zone 3-supporting
confidence: 92%
“…In fact on the average there was a slight increase in PVR as pulmonary arterial pressure was raised, while there was a slight decrease as pulmonary venous pressure was raised, but in both cases the changes were very small and not statistically significant. This is very different behavior from that seen in the mammalian lung where both increases in pulmonary arterial pressure or pulmonary venous pressure result in large falls in PVR (Haddy and Campbell 1953;Borst et al 1956;Lloyd and Wright 1960;Roos et al 1961). The mechanism of the fall in PVR is believed to be mainly the recruitment and distension of pulmonary capillaries that occurs when the pressure inside them is increased, and this behavior has been demonstrated histologically (Glazier et al 1969).…”
Section: Rigidity Of the Pulmonary Capillaries In The Chickenmentioning
confidence: 90%
See 2 more Smart Citations
“…The fact that many patients have normal PVR may be partly due to passive distention of pulmonary resistance vessels due to pulmonary venous hypertension. 41,42 Considerable note has been made of PH "out of proportion" to the magnitude of LA pressure (i.e., a transpulmonary gradient >12 mmHg). 40,43 Some observers even suggest that this disproportionate increase in PAP may be due to factors independent of the PVH.…”
Section: Causes Of Pvhmentioning
confidence: 99%